Super Broadband at Telecom Wavelengths From RE3+-Doped SiO2-Ta2O5 Glass Ceramics Planar Waveguides - De Oliveira Lima, Karmel; Caixeta, Fábio José; Souza, Vítor Dos Santos De; Rosa, Leonardo Sousa; Soares, Victor Del Vecchio; Crumo, Carolina Assunção; Borin, Ivana Aparecida; Ferrari, Jefferson Luis; Gonçalves, Rogéria Rocha (Frontiers in Chemistry, 2022)
This paper reports on the preparation of Er3+/Yb3+/Tm3+, Er3+/Yb3+/Nd3+, and Er3+/Tm3+/Nd3+ triply doped and Er3+-doped SiO2-Ta2O5 glass ceramic nanocomposites and active planar waveguides by the sol–gel process using the dip-coating technique as deposition method. The investigation of their structural, morphological, and luminescent properties using XRD, AFM, and photoluminescence analysis, are reported here. The XRD results showed the presence of L-Ta2O5 nanocrystals dispersed in the SiO2-based amorphous host for all the nanocomposites and films. The rare earth ion (RE3+) doping concentration affected both the crystallinity, and the crystallite sizes of the Ta2O5 dispersed into SiO2-Ta2O5 nanocomposites and waveguides. AFM characterization revealed crack free and smooth surface roughness and differences in viscoelasticity on the Er3+-doped SiO2-Ta2O5 films surface, which allows the identification of Ta2O5 nanocrystals on the SiO2 amorphous host. The Er3+ doped and triply doped SiO2-Ta2O5 nanocomposites displayed broad- and super broadband NIR emissions with a FWHM up to 173 nm achieved in the telecom wavelengths. The lifetime of the 4I13/2 emitting level of the Er3+-doped SiO2-Ta2O5 waveguides is strongly dependent on Er3+ concentration and an emission quenching was negligible up to 0.81 mol%. The structural and luminescent investigations indicated that RE3+-doped SiO2-Ta2O5 glass ceramics are promising candidates for photonic applications in optical devices operating in wide wavelengths at the telecom bands.